“They Weren’t Necessarily Designed with Lived Experiences of Disability in Mind”: The Affect of Archival In/Accessibility and “Emotionally Expensive” Spatial Un/Belonging - Brilmyer, Gracen (Archivaria)

(untitled) (Association of Canadian Archivists, 2022)
Using semi-structured interviews with disabled archival users and building on the emerging field of critical access studies, this article illustrates the ways in which archival spaces and their in/accessibility affectively impact disabled people. Interviewees describe how they experience barriers to accessibility not only at a basic, architectural level – of not being able to get into a building or archives room – but also through archives’ policies and expectations regarding the ways in which archival work is done. The way that accessibility is implemented, even beyond legal compliance, greatly impacts the extent to which disabled researchers feel they belong in archival spaces. Inaccessibility, this research shows, produces a sense of unbelonging; the deprioritization of disability both as a subject or organizing category and as an identity of a potential researcher, shows disabled people that they do not belong in archival spaces, and this is further complicated for multiply marginalized disabled people. By examining the multifaceted ways that disabled people experience inaccessibility, this article focuses on the “emotionally expensive” aspects of inaccessibility to emphasize the ways in which barriers compound and accumulate and can prevent disabled people from accessing our own histories. These findings demonstrate how central accessibility is to disabled people’s lives: it is almost impossible to talk about our experiences of archival materials and history without discussing how we navigate the multiple barriers to accessing them.